Synthesis of Complex Phenols Enabled by a Rationally Designed Hydroxide Surrogate. (24th March 2017) - Fier, Patrick S.; Maloney, Kevin M.
Abstract: The conversion of aryl halides to phenols under mild reaction conditions is a longstanding and formidable challenge in organic chemistry. Herein, we report the rational design of a broadly applicable Pd‐catalyzed method to prepare phenols with benzaldehyde oxime as a hydroxide surrogate. These reactions occur under mildly basic conditions and enable the late‐stage hydroxylation of several functionally‐dense drug‐like aryl halides.